Crohn's and Colitis Canada's 2021 Impact of COVID-19 and Inflammatory Bowel Disease in Canada: Epidemiology—The Trends of Disease Over Time. (5th November 2021) - Coward, Stephanie; Windsor, Joseph W; Kuenzig, M Ellen; Bitton, Alain; Bernstein, Charles N; Jones, Jennifer L; Khanna, Reena; Lee, Kate; Murthy, Sanjay K; Targownik, Laura; Benchimol, Eric; Huang, James Guoxian; et al.
Abstract: At the beginning of the coronavirus disease 2019 (COVID-19) pandemic, there were many unknowns: transmission vectors of the virus, appropriate intervention strategies and if being immunocompromised due to inflammatory bowel disease (IBD), for example, or medications put a person at increased risk for severe COVID-19. Imposing and relaxing of public health restrictions at different times and in different regions in Canada led to different epidemiologies of the virus in different provinces and territories. In order to understand the waxing and waning of waves of the COVID-19 pandemic, it is necessary to understand the effective reproductive number ( R t ) and the countervailing forces that exert upward or downward pressure on the spread of the virus at a given point in time. As many regions in Canada deal with a third wave, the primary forces affecting the R t of severe acute respiratory syndrome coronavirus 2 are variants of concern and the increasing vaccinations of Canadians leading to increased population-level immunity. Fortunately, for the IBD population, current research suggests that those with IBD are not at increased risk of contracting COVID-19, nor of having a more severe disease course when compared to the general population.